Aktualisasi Ketubuhan Perempuan dan Representasi Estetika Hindu Dalam Tari Rejang Pedawa - Nyoman Suardika (Jurnal Penelitian Agama Hindu, 2026)
The Rejang Pedawa dance is performed by young women who have reached adolescence but have not yet experienced their first menstrual cycle. This dance movement represents a sense of boundary (the concept of limits or barriers), the dimensions of the female body, Hindu esthetics, body-based worship schemes, and the esthetic aspects of liturgical behavior. The purpose of this research is to analyze philosophically and esthetically the medium of worship that is actualized thru the female body. This research applies a qualitative method within a case study framework. Data was collected thru interviews, observations, and literature reviews. The female body, used as a medium for dance movements and the ideology of worshiping a transcendent entity, represents the actualization of natural or supernatural elements. The body movements of the Rejang Pedawa dance create women's ability to channel cosmic energy, incorporate the world, and reflect the interdependence between humans and God (Dewa Indra). The Hindu esthetics in this dance are perceived as a manifestation of artistic experiences that have been internalized into both the personal and communal aspects of the local community, the people of Pedawa Village. The actualization of the village’s characteristic rejang dance demonstrates a way of seeing, thinking, and total surrender to the Almighty entity. The movements of each dancer are used as a bridge between the human world and the divine world, a process of total surrender within an integral scope, becoming a visualization of a sacred arena realized thru the beauty of movement.